Complex Basement‐Involved Contractional Structures in the Pre‐Andean Basins of Northern Chile: A Review From Seismic Data. Issue 2 (18th February 2021) - Martínez, F.; Muñoz, B.; López, C.; González, R.; Parra, M.; Riquelme, R.
Abstract: For many years, the geometry, kinematic, and the age of the basement‐involved structures of the Pre‐Andean basins of northern Chile have been debated. Even, many tectonic models supported by surface geological data have ignored how is the continuity of these structures in the subsurface, and also their possible relation with ancient preorogenic structures, thus difficulting the understanding of the main tectonic mechanisms that acted during the Andean uplift. To solve this problem, we discussed in this study the geometry and timing of the basement‐involved contractional structures present in the Pre‐Andean basins of northern Chile. We present field and seismic evidences of different basement‐involved structural styles, including reverse faults, inverted normal faults, basement thrust ramps, and rotated and reworked basin margins, and use it them to produce three large structural cross‐sections showing the geometries and distribution of structures along the inner forearc region. The structures are interpreted to have resulted from basin inversion, which was followed by large reverse faulting accumulating 43 km in the Salar de Atacama, 10 km in the Salar de Punta Negra, and 27 km in the Salar de Pedernales. Major reverse faults are predominantly located along the western and eastern edges of the basins, whereas inverted normal faults, basement thrust ramps, and other structures are confined to the central sections. In this context, large basement thrust ramps and reverse faults are the most effective structures for generating crustal thickening. Previous analyses (U‐Pb dating) of synorogenic deposits over inverted structures and apatite fission track data from Paleozoic basement prerift rocks suggest that contraction in the region began in the Late Cretaceous‐Paleocene and continued throughout the Cenozoic; however, basement rocks experienced rapid cooling due to tectonic uplift during the Eocene. Further, the results indicate that basement‐involved contractional structures are not only generated by flat‐slab subduction processes, but also observed in other regions of northern Chile (e.g., Frontal Cordillera). Finally, we conclude that the observed structural complexity predominantly results from the initial distribution of preorogenic extensional structures. Key Points: We present the first restoration of three regional cross‐sections that show the distribution, geometry, and kinematics of contractional structures along the inner forearc region at northern Chile Late Cretaceous basin inversion Basement‐involved contractional faults and folds are strongly controlled by the reactivation of previous zones of crustal weakness in the upper crust